Sv. Marjeta Marija Alacoque v umetnosti na Slovenskem - Lavrič, Ana (Acta ecclesiastica Sloveniae, 2024)
Following the introductory presentation of the iconography of the Sacred Heart connected to the visions of Margaret Mary Alacoque, the article briefly introduces the typology of Margaret’s depictions on the path from her historical to saintly character, illustrated with some examples from European art. The presentation of the Slovenian material combines chronological and typological aspects. It begins with the most frequent motif of Jesus appearing to Margaret (Kamnik, Novo mesto, Celje, Brestanica), but discusses the scene on the stained-glass windows separately (Ljubljana, Mengeš, Drežnica), followed by examples of the individual depictions of the mystic on the altars (Kranjska Gora, Brestanica, Maribor) and a group scene in which she worships the Sacred Heart together with Slovenians (Ivan Grohar: Ljubljana and Begunje; Ivan Vavpotič: Brezje). Even given the limited territory included, it is clear that depictions in Slovenia are rare, that they appear fairly late (the first supposedly in 1876), and in a very limited time period. These are works of local Late Nazarene painters (Matija Koželj, Matija Bradaška, Peter Markovič), while several pieces were purchased from foreign art institutions, e.g. in Tyrol, in Munich, Paris, and Pietrasanta near Carrara (stained glass, a few statues, and a relief). The pieces are mostly of stencil. The motif came to life artistically only with Ivan Grohar and Ivan Vavpotič, with both with an emphasised national note, while it was later personally interpreted by Tone Kralj (Šturje).
Keywords: Alacoque, Marguerite Marie; Grohar, Ivan; iconography; ikonografija; Sacred Heart; Slovenian art; Srce Jezusovo; Vavpotič, Ivan